# 3x 5x 1 ## Linear equations with one unknown

### Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

3*x-5*x-(1)=0

### Step  1  :

#### Pulling out like terms :

Pull out like factors :

-2x - 1  =   -1 • (2x + 1)

### Step  2  :

#### Solving a Single Variable Equation :

Solve  :    -2x-1 = 0

Add  1  to both sides of the equation :
-2x = 1
Multiply both sides of the equation by (-1) :  2x = -1

Divide both sides of the equation by 2:
x = -1/2 =

### One solution was found :

x = -1/2 =
Sours: https://www.tiger-algebra.com/drill/3x-5x=1/

## What is the result of adding -3x -5x 1 and 8x - 2x - 9?

Am I right :P?5x^(3)-3x+x^(3)-2x+6x-1Since 5x^(3) and -3x^(3) are like terms, add -3x^(3) to 5x^(3) to get 2x^(3).(d)/(dx) 5x^(3)-3x+x^(3)-2x+6x-1=2x^(3)-3x+x+6x-1Since -3x and -2x are like terms, subtract 2x from -3x to get -5x.(d)/(dx) 5x^(3)-3x+x^(3)-2x+6x-1=2x^(3)-5x+4+6x-1Since -5x and 6x are like terms, subtract 6x from -5x to get x.(d)/(dx) 5x^(3)-3x+x^(3)-2x+6x-1=2x^(3)+x+Subtract 1 from 4 to get 3.(d)/(dx) 5x^(3)-3x+x^(3)-2x+6x-1=2x^(3)+x+3To find the derivative of 2x^(3), multiply the base (x) by the exponent (3), then subtract 1 from the exponent.(d)/(dx) 5x^(3)-3x+x^(3)-2x+6x-1=6x^(2)+(d)/(dx) x+3To find the derivative of x, multiply the base (x) by the exponent (1), then subtract 1 from the exponent (=0). Since the exponent is now 0, x is eliminated from the term.(d)/(dx) 5x^(3)-3x+x^(3)-2x+6x-1=6x^(2)+1+(d)/(dx) 3Since 3 does not contain x, the derivative of 3 is 0.(d)/(dx) 5x^(3)-3x+x^(3)-2x+6x-1=6x^(2)+1+0Add 0 to 1 to get 1.(d)/(dx) 5x^(3)-3x+x^(3)-2x+6x-1=6x^(2)+1The derivative of 5x^(3)-3x+x^(3)-2x+6x-1 is 6x^(2)+x^(2)+1

## 3x(5x-1)=

### Solution for 3x(5x-1)= equation:

Simplifying 3x(5x + -1) = 0 Reorder the terms: 3x(-1 + 5x) = 0 (-1 * 3x + 5x * 3x) = 0 (-3x + 15x2) = 0 Solving -3x + 15x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x'. 3x(-1 + 5x) = 0 Ignore the factor 3.

#### Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

#### Subproblem 2

Set the factor '(-1 + 5x)' equal to zero and attempt to solve: Simplifying -1 + 5x = 0 Solving -1 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 5x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = 0 + 1 5x = 0 + 1 Combine like terms: 0 + 1 = 1 5x = 1 Divide each side by '5'. x = Simplifying x =

x = {0, }

### See similar equations:

| 6n=+n || 7x-(-2)=30 || 6x^x+=0 || x^x=-8 || 14=8+6b || (5+v)(2v-9)=0 || x+(x)=() || c= || 16(x-4)=4(x+36) || 4(x+4)=3x+9 || a=m+ || x=3(2x+4)-x || (x+2)=(2x-4) || 9a-2(6a+3)= || 4x-7(-4x-7)= || 4x+3=32 || 3(x+9)=2x+19 || 2x+6x-1=3 || 7(x-4)=6x || 3(x+6)=9x-6 || =s+ || x^x+49=78 || 3c-8+6-c= || 3x^x=0 || m= || 23a=34a || 7w^2+18w+8=0 || 6x(4x^2+1)x^2(2x-1)=0 || 2(x-8)= || 2a+7=a-4 || 5x^x+63=0 || 24x=33 |

Sours: https://www.geteasysolution.com/3x(5x-1)=
How To Factor Polynomials The Easy Way!

## 3x(5x-1)=

### Solution for 3x(5x-1)= equation:

Simplifying 3x(5x + -1) = 0 Reorder the terms: 3x(-1 + 5x) = 0 (-1 * 3x + 5x * 3x) = 0 (-3x + 15x2) = 0 Solving -3x + 15x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x'. 3x(-1 + 5x) = 0 Ignore the factor 3.

#### Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

#### Subproblem 2

Set the factor '(-1 + 5x)' equal to zero and attempt to solve: Simplifying -1 + 5x = 0 Solving -1 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 5x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = 0 + 1 5x = 0 + 1 Combine like terms: 0 + 1 = 1 5x = 1 Divide each side by '5'. x = 0.2 Simplifying x = 0.2

x = {0, 0.2}

### See similar equations:

| 6n-14=-24+n || 7x-(-2)=30 || 6x^2-51x+105=0 || x^2-8x=-8 || 14=8+6b || (5+v)(2v-9)=0 || 0.55x+.05(20-x)=.10(-20) || -4.6c=27.6 || 16(x-4)=4(x+36) || 4(x+4)=3x+9 || a=136m+225 || x=3(2x+4)-x || (x+2)=(2x-4) || 9a-2(6a+3)= || 4x-7(-4x-7)=-111 || 4x+3=32 || 3(x+9)=2x+19 || 2x+6x-1=3 || 7(x-4)=6x-23 || 3(x+6)=9x-6 || 1.18=s+3.09 || x^2-14x+49=78 || 3c-8+6-c= || 3x^2-15x-198=0 || -17.2m=159.96 || 23a-34=34a || 7w^2+18w+8=0 || 6x(4x^2+1)-15x^2(2x-1)=0 || 2(x-8)=-10 || 2a+7=a-4 || 5x^2-52x+63=0 || 24x=33 |

Sours: https://www.geteasysolution.com/3x(5x-1)=

## Linear equations with one unknown

### Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

3*x-5*x-(1)=0

### Step  1  :

#### Pulling out like terms :

1.1     Pull out like factors :

-2x - 1  =   -1 • (2x + 1)

### Step  2  :

#### Solving a Single Variable Equation :

2.1      Solve  :    -2x-1 = 0

Add  1  to both sides of the equation :
-2x = 1
Multiply both sides of the equation by (-1) :  2x = -1

Divide both sides of the equation by 2:
x = -1/2 = -0.500

### One solution was found :

x = -1/2 = -0.500
Sours: https://www.tiger-algebra.com/drill/3x-5x=1/
Numbers with different speeds (1/10x, 1/5x, 1/2x, 1x, 2x, 3x, 5x and 10x)  ### Most Used Actions

 \mathrm{simplify} \mathrm{solve\:for} \mathrm{inverse} \mathrm{tangent} \mathrm{line}
Related »Graph »Number Line »Examples » Our online expert tutors can answer this problem

Get step-by-step solutions from expert tutors as fast as minutes. Your first 5 questions are on us!

In partnership with

You are being redirected to Course Hero

Let's Try Again :(

Try to further simplify ### Examples

step-by-step

-x+2+3x=5x-1

en

Sours: https://www.symbolab.com/solver/step-by-step/-x%2B2%2B3x%3D5x-1?or=popular

### Now discussing:

.

133 134 135 136 137